CLIMATE CHANGE IMPACTS ON AGRICULTURE AND HOUSEHOLD FOOD SECURITY IN KAZUNGULA DISTRICT - Ambukeg, Lusajo M; Sakala, Enock (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2017)
The study assesses the nature and impacts of climate change induced hazards on agriculture and food security as well as the coping strategies of vulnerable households to climate change. The study shows that climate change is a major problem to agriculture, household food security and rural livelihoods for majority of the households in Kazungula district. Survey findings suggests that climate change is real and parameters such as temperature and rainfall have changed in the last 30 years (1963- 1993) affecting crop production negatively. Temperature has increased by 2° C while rainfall has decreased by 130mm. Climate change has impacted negatively on agriculture and the four pillars of food security (access, utilization, availability and stability). Survey findings indicate that 64 percent of the households were exposed to climate change, youth headed households (44 percent) were less vulnerable to the impacts of climate change compared to the elderly (56 percent) headed households. Majority of the households were highly dependent on emergency and crisis coping strategies. The study strongly recommends promotion and adoption of long-term adaption strategies to build the adaptive capacity of local communities